Mother's knowledge and attitudes towards Visual Acetate Acid Inspection test in Surabaya - Dini Mei Widayanti; Mochammad Bagus Qomaruddin; Dedi Irawandi (SAGE Publishing, 2020)
Background: The incidence of cervical cancer in Indonesia is still high due to the poor awareness of married women about the necessity to check themselves with a pap smear/IVA test for early detection and possible cure. The implementation of the IVA examination still experiences obstacles due to lack of knowledge and fear. Design and Methods: This study aims to determine the relationship between knowledge and attitudes of mothers with IVA test, using the analytical and cross-sectional study. Data were obtained from mothers that visited the family planning section of the Maternal and Child Health (MCH) Center. Out of a total of 184 mothers, 126 samples were chosen by purposive sampling technique. Results: The results showed that 59.5% of respondents had scarce knowledge on IVA tests, 66.7% had unsupportive attitudes towards it, and 54.8% were not willing to carry out the tests. This study explains that there is a significant relationship between knowledge and attitude with a P-value of 0.000. Conclusions: In conclusion, various factors influence the participation of IVA examination, namely lack of knowledge, inability to access information, and fear.